Primary Hepatic Burkitt Lymphoma - Gentile, João Kleber de Almeida; Renesto, Beatriz; Miléo, Luis Fernando Alves; Oliveira, André Cosme de; Patzina, Rosely Antunes; Ponce, César Cilento; Braga, Walter Moises Tobias (Brazilian Journal of Case Reports, 2023)
The liver is an uncommon primary site for lymphoma, comprising only 0.4% of extranodal lymphomas, and liver involvement is almost always secondary to systemic lymphoma. Primary hepatic lymphoma has been reported to occur more frequently in immunosuppressed patients, especially with chronic hepatitis C infection, and may be associated with hepatitis B infection and the Epstein-Barr virus. Patients usually present with pain or a mass in the right upper quadrant, with or without jaundice, and it is more common in middle-aged males. The diagnosis of extranodal lymphoma or primary hepatic lymphoma can be difficult, especially in people living with human immunodeficiency virus (HIV) positivity or acquired immunodeficiency syndrome (AIDS). Due to its rarity, it is often overlooked as a possible differential diagnosis, with nonspecific imaging findings and a definitive diagnosis made only after anatomopathological and immunocytochemical examination. We present a rare case of Burkitt’s lymphoma presenting as liver masses.